Modified trapdoor procedures by surgical dislocation approach to treat chondroblastoma of the femoral head. (June 2019) - Liu, Q.; He, H-B.; Zeng, H.; Yuan, Y-H.; Long, F.; Tian, J.; Luo, W.
Abstract : Aims: The aim of this study was to evaluate the efficacy of the surgical dislocation approach and modified trapdoor procedure for the treatment of chondroblastoma of the femoral head. Patients and Methods: A total of 17 patients (ten boys, seven girls; mean age 16.4 years (11 to 26)) diagnosed with chondroblastoma of the femoral head who underwent surgical dislocation of the hip joint, modified trapdoor procedure, curettage, and bone grafting were enrolled in this study and were followed-up for a mean of 35.9 months (12 to 76). Healing and any local recurrence were assessed via clinical and radiological tests. Functional outcome was evaluated using the Musculoskeletal Tumour Society scoring system (MSTS). Patterns of bone destruction were evaluated using the Lodwick classification. Secondary osteoarthritis was classified via radiological analysis following the Kellgren–Lawrence grading system. Steinberg classification was used to evaluate osteonecrosis of the femoral head. Results: The epiphyseal plate was open, closing, and closed in five, five, and seven patients, respectively. In total, eight, six, and three patients were classified as having Lodwick classification IA, IB, and IC, respectively. Allogeneic and autogenous bone grafting was used in 13 and four patients, respectively. All patients had good bone healing and no local recurrence was observed. One patient developed osteonecrosis of the femoral head (Steinberg IA) and one developed secondary osteoarthritis of the hip joint (Kellgren–Lawrence Grade II). The mean postoperative MSTS functional score was 27.7 (24 to 30). Conclusion: Surgical dislocation and modified trapdoor procedures are safe and effective techniques for treating chondroblastoma in the femoral head. Cite this article: Bone Joint J 2019;101-B:732–738.